2021
DOI: 10.1088/1757-899x/1090/1/012097
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of flow pattern in an open channel with sidewall obstruction

Abstract: To predict flow pattern of shallow obstructed open channel flows, laboratory experiments of flow around a vertical emergent sidewall abutment (lateral constriction) in an open channel flow is simulated numerically and results of water surface and vertical profile of velocity are compared with the numerical results. The turbulence kinetic energy at the separation zone and bed shear stresses are also investigated. A computational fluid dynamic (CFD) numerical tool and volume of fluid (VOF) were used to predict w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Their findings suggested that altering the bridge piers' position in the channel had an insignificant effect on the value of the maximum scour, while the value of the maximum sedimentation rose by 12% when the piers were displaced from 60 degrees to 90 degrees; however, moving them from 90 to 120° entailed a 42% decrease in the maximum sedimentation [14] 2021) developed a numerical model of the flow around a vertical emergent sidewall abutment in an open channel flow, eventually showing a good match between experimental and numerical results of the water surface profiles. They showed that increasing discharge increased the maximum pressure in front of the constriction [27]. explored the scour around a triad series of vertical piers in a bend.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggested that altering the bridge piers' position in the channel had an insignificant effect on the value of the maximum scour, while the value of the maximum sedimentation rose by 12% when the piers were displaced from 60 degrees to 90 degrees; however, moving them from 90 to 120° entailed a 42% decrease in the maximum sedimentation [14] 2021) developed a numerical model of the flow around a vertical emergent sidewall abutment in an open channel flow, eventually showing a good match between experimental and numerical results of the water surface profiles. They showed that increasing discharge increased the maximum pressure in front of the constriction [27]. explored the scour around a triad series of vertical piers in a bend.…”
Section: Introductionmentioning
confidence: 99%